Bee venom loaded nanomaterials for cancer therapy: a novel approach - Vikram Jadhav; Arun Bhagare; Arpita Roy; Dnyaneshwar Lokhande; Shaktising Pardeshi; Jayraj Aher (Discover Materials)
Abstract Cancer remains a leading cause of death worldwide, underscoring the urgent need for innovative treatment strategies. While conventional cancer therapies are constrained, nanotechnology offers exciting opportunities for targeted and effective cancer treatments. The potential of bee venom—a naturally occurring substance known for its anti-cancer effects—to improve treatment outcomes has attracted considerable interest. This review article examines the creation and use of bee venom-loaded nanomaterials as a novel method for cancer targeting. By incorporating bee venom into nanomaterials, its release can be controlled, leading to better bodily distribution. Additionally, encapsulating bee venom within nanomaterials can amplify its cytotoxic effects on cancer cells and enhance its anti-inflammatory and immunomodulatory properties. Various nanomaterials, including liposomes, polymeric, and inorganic nanoparticles, have been explored to deliver bee venom. These nanomaterials offer numerous benefits, such as lower systemic toxicity, targeted delivery to tumor sites, and improved solubility. Bee venom-loaded nanomaterials (BVNMs) employ various mechanisms to combat cancer. Key components of bee venom, including melittin, apamin, and phospholipase A2, induce apoptosis in cancer cells. Consequently, with the enhanced effectiveness of existing therapies and targeted strategies addressing specific pathological pathways, using BVNMs can significantly improve patient outcomes, making this approach a highly promising tactic in the fight against cancer medicine. Applying nanotechnology and harnessing the unique properties of venom may improve therapeutic efficacy while reducing toxicity and facilitating targeted drug delivery. Further research and development in this area are essential to fully harnessing the therapeutic potential of BVNMs and improving the quality of life for individuals affected by cancer. The review paper highlights the importance of the scientific community continuing to explore the possibility of BVNMs, thus encouraging researchers to contribute to this crucial field. Graphical Abstract